(3GdeNJQY aj afhf ef GdUfYs - (3YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd, CHh MaU, eegO GdOjf, Gdedc GdCTQa,J (B696 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH LeYJ ajg WQakG ef GdUfGYGJ hSejJg GdeNJQY aj afhf ef GdUfY s
(3BNQgG (B:s
(3dYOe GSJYeGd Cgd CQVfG dcPdc hGddg Gdehab Edi QVGg hgh MSHfG hfYe Gdhcjd hfYe Gdehdi hfYe GdfUjQ s
(3GdfSNI HgG MhGTs
(3JcQQJ CjVkG JMJ Qbe (B25 (3UfGYI hCWYeIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B6s
Keywords: (3GdUfGYI hGdCWYeIs